Konsep Haqiqah dan Majaz dalam Ushul Fiqh dan Implikasinya terhadap Istinbath Hukum - Anita Safitri; Izah Ririn Sapitri; Erli Anggraini Putri (CV. ITTC INDONESIA, 2025)
This study aims to analyze the concepts of haqiqah (literal meaning) and majaz (figurative meaning) in Ushul Fiqh and their implications in the determination of Sharia law. The study is motivated by the issue that misunderstanding the difference between these meanings often affects the legal conclusions derived from Qur’anic and Prophetic texts. The research employs a qualitative-descriptive approach through library research on classical works by scholars such as Al-Amidi, Al-Ghazali, Al-Razi, Asy-Syaukani, Ibn Manzur, and Al-Jurjani. The findings indicate that distinguishing between literal and figurative meanings is a crucial step in deriving rulings from Qur’anic and Hadith texts. The meaning of haqiqah is always prioritized unless there is qarinah requiring a shift to majaz. The study concludes that the concepts of haqiqah and majaz serve as methodological instruments to ensure accuracy, consistency, and contextual relevance in Islamic legal reasoning.